Mapeamento geotécnico do setor norte do município de Goiânia-GO, em escala 1/25.000 - Martins, Antônio Henrique Capuzzo (2005)
This research presents a engineering geological mapping of the north portion of the city of Goiânia in the area that was proposed as a new perimeter of the urban expansion of the city, in the new main plan of Goiânia. The work was developed in the scale 1:25.000 and the methology of engineering geological mapping elaborated by Zuquette(1987). The physical environment chacaracteristics were obtained as a final product and they were based in the Goiânia 1981 risk chart, laboratory tests and fild works. Some of them were analyzed together with the photo- interpretation works, characterization test reports of the area. Thus, six cartographic documents were elaborated: Documentation map, geological bedrock map, unconsolidated material map, freatic water level map, declivities map and geotecnical units were elaborated.